Effect of behavioural intention toward choosing green hotels in Malaysia - Preliminary study - Nezakati, Hossein *; Shayesteh, Moghadas; Yuhans, Abdul Aziz; Asra, Aimidi; Roghayeh, Sohrabinezhadtalemi; Yusmadi, Yah Jusoh (Elsevier, 2015)
Based on Economic transformation programme of Malaysia Tourism and hospitality are one of the significant factors which effect on economy for achieving the vision of Malaysia 2020. In other hand, Rapid growths of these industries have effect on environment. This research tries to propose a new model by merging Theory Reasoned Action and Theory Planned Behaviour models which are implemented in achieving intention of consumer behaviour toward choosing Green hotels in Malaysia. Findings of this research will help the marketing policy makers and hotel managers to attract positional tourists who will visit Green hotels in Malaysia.